Knowledge, Perception, and Practice of Libyan Mothers towards Varicella and Its Vaccination Tripoli, Libya - Ehmeid Khalifa,; Hadil Musa,; Aisha Benrween,; Mohammed Alnaami,; Asraa Areebi, (AlQalam Journal of Medical and Applied Sciences, 2024)
This study was conducted to ascertain the level of knowledge, perception and practice towards chickenpox infection and its vaccination and to find out the relationship of knowledge to some of related characteristics of the mothers and their children. A cross sectional study was conducted among Libyan mothers in Albadri polyclinic the east district of Tripoli. Data analysis was performed using the SPSS version 26. A total of 204 Libyan mothers attending Albadri polyclinic participated in the study their mean age was 32.06 (± 7.664) years. Most of the respondents (95.6%) had heard about chickenpox and (84%) stated correctly about its mode of transmission. Majority were well aware of the signs and symptoms of the infection, (51%) of the respondents knew about chickenpox vaccination, and only (43.1%) have been known that the vaccine was available in Libya. Concerning perception (81.4%) of respondents had negative perception about their child might get chickenpox. (80.9%) of the respondents were agree about their believing that chickenpox is serious disease and only 12.3% respondents believed that vaccine was effective, (77.9%) of respondents had negative perception about safety of vaccine. Concerning practice approximately (80%) of the respondents had vaccinated or had intension for vaccination their children against chickenpox. The current study indicated considerable knowledge levels and practice on varicella disease and its vaccination were observed among Libyan mothers. Addressing concerns regarding vaccine effectiveness, safety and importance through educational campaigns to ensure that all mothers are informed of the availability and benefits of the varicella vaccine يعد الحماق (ابوشوكة) أحد الأمراض الفيروسية الأكثر شيوعًا والأكثر عدوى في مرحلة الطفولة، وقد ثبت أن استخدام اللقاح الوقائي للأطفال آمن وفعال في الحد من الإصابة والمراضة المرتبطة به. هدفت هذه الدراسة إلى التأكد من مستوى المعرفة والإدراك والممارسة تجاه الإصابة بجدري الماء والتطعيم ضده ومدى امكانية وجود علاقة مع بعض الخصائص لدى الأمهات واطفالهن. أجريت هذه الدراسة المقطعية على عينة من الأمهات الليبيات اللاتي ارتدن مستوصف البدري بالناحية الشرقية لمدينة طرابلس. تم إجراء تحليل البيانات باستخدام الإصدار 26 من برنامج SPSS. شارك في الدراسة إجمالي 204 من الأمهات الليبيات اللاتي ارتدن مستوصف البدري، وكان متوسط أعمارهن 32.06 (± 7.664) سنة. معظم المشاركين (95.6%) لديهم خلفية عن جدري الماء (أبوشوكة)، وكان (84%) منهم قد تكونت عنده فكرة صحيحة عن كيفية انتقاله. أما بالنسبة لاعراض وعلامات العدوى فـ كان أغلبهم على دراية تامة بها. وعلى الرغم من أن (51%) من المستجيبين لهذه الدراسة يعرفون عن تطعيم جدري الماء، إلا أن (43.1%) منهم فقط كانوا على دراية بتوفر اللقاح في ليبيا. كما أن (81.4%) من الأمهات كان لديهم تصور سلبي عن قابلية حدوث نتائج سلبية على أطفالهم بحيث يكون هذا التطيعم هو مصدر للعدوى بـ جدري الماء (ابوشوكة). ويعتقد حوالي (80.9%) من أفراد العينة أن جدري الماء (أبوشوكة) هو مرض خطير ومعدي وكان منهم (12.3%) يعتقد بأن اللقاح ذو فاعلية عالية، بينما (77.9%) منهم كان لديه تصور سلبي بشكل عام حول سلامة اللقاح. وأشارت النتائج المتعلقة بالمعرفة العملية عن اللقاح أن ما مجموعه (80%) من أفراد العينة كانوا بين من قام بالفعل بتطعيم طفله أو لديه رغبة في تطعيم طفله ضد مرض الجدر (ابوشوكة). أشارت الدراسة الحالية إلى وجود مستويات كبيرة من المعرفة والممارسة حول مرض الحماق والتطعيم ضده بين الأمهات الليبيات، مع معالجة المخاوف المتعلقة بفعالية اللقاح وسلامته وأهميته من خلال الحملات التثقيفية لضمان إعلام جميع الأمهات بتوفر لقاح الحماق وفوائده